PROBLEMATIKA PEMBERIAN PERLINDUNGAN INVESTOR DALAM PERJANJIAN INVESTASI BILATERAL INDONESIA - Sidik, Rahmat Maulana (BULETIN KONSTITUSI, 2023)
Abstract The BIT (Bilateral Investment Treaty) is a legal umbrella in guaranteeing investment in the host country. Generally, these agreements are made to attract more investors both from within and outside the country for the sake of economic improvement and development. The crucial issue is when the BIT provides full facilities for investors without considering whether the provision of investment protection threatens the sovereignty of the state and peoples in the future or not. In the fact, will the policy actually attract more investment into the destination country or will it become a legal loophole for unruly investors in taking advantage of the legal loopholes in BIT agreements. It is only natural that these kinds of questions arise as a form of public dissemination or facts that occur directly. Because this BIT not only guarantees protection for investment, but also provides flexibility for investors to sue the state if their investment is harmed by the policies of the recipient country of investment. Even this investment dispute settlement mechanism is guaranteed through ISDS (investor-state dispute settlement). Where the ISDS clause provides guarantees for investors to sue the state in international arbitration. This clause does not apply vice versa for the state in suing investors who harm the state and the peoples. If so, then the provision of excessive investment protection with the ISDS clause in this BIT has the potential to threaten the sovereignty of the state and people. This research will review the case of investor lawsuits against Indonesia and impacted in a crisis of legitimacy over policies made by the state. Including highlighting the protection of investors and the ISDS mechanism whether it is constitutionally contradictory or not.